Contribution to the experimental and theoretical study of the behavior of soil-structure interfaces - Saliha Benalia; Boubaker Benchiekh; Leila Zeghichi (The Journal of Engineering and Exact Sciences)
Designing civil engineering works often requires taking into consideration the contact and interface conditions between the soil and structure. These may refer to the discontinuity surfaces between the soil and a structure such as foundations, geotechnical works, and others. Current research aims to improve the calculation methods for structures through a better understanding of the behavior of materials and interfaces. The present work falls into this context. It involves two parts. The main purpose of the first part is to present the results of the monotonic and cyclic soil-structure interface tests which were carried out using a modified direct shear box apparatus. The tests were conducted using a local material, namely the sand from the town of Messâad in the Wilaya of Djelfa (Algeria), in accordance with a constant normal stress path. In addition, a parametric study, dealing with the effect of density, interface roughness, and type of adhesive used on the behavior of the interfaces, was carried out as well. As for the second part, it primarily aims to validate the Modjoin interface model, which was developed at the Lille Mechanical Laboratory, based on the tests that were carried out in the first part. It is important to know that this model includes the main concepts used in soil modeling, such as isotropic hardening, characteristic state, critical state, softening, and others. Moreover, several validation tests are also presented in this work in order to describe the behavior of the soil-structure interface under monotonic loading to assess the performance of the model.